(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2023)
This study looks at married women’s experiences with social work interventions and social group work to see how they might help them achieve a healthy work-life balance in the workplace. Finding and implementing successful strategies that cover both the professional and personal spheres is the objective of this study, given that this specific group faces very challenging difficulties. The two most common research designs are the descriptive design and the quasi-experimental design. The features of the trials that are being studied may be described using the descriptive design. Researchers were able to secretly administer the intervention to the treatment group while concealing it from the control group because to this design. This study article looks at the effects on health of work-life conflicts.